Basket trials in oncology: a systematic review of practices and methods, comparative analysis of innovative methods, and an appraisal of a missed opportunity - Kasim, Adetayo; Bean, Nathan; Hendriksen, Sarah Jo; Chen, Tai-Tsang; Zhou, Helen; Psioda, Matthew A. (Frontiers in Oncology, 2023)
Basket trials are increasingly used in oncology drug development for early signal detection, accelerated tumor-agnostic approvals, and for prioritization of promising tumor types in selected patients with the same mutation or biomarker. Participants are grouped into socalled baskets according to tumor type, allowing investigators to identify tumors with promising responses to treatment for further study. However, it remains a question as to whether and how much the adoption of basket trial designs in oncology have translated into patient benefits, increased pace and scale of clinical development, and de-risking of downstream confirmatory trials. Innovation in basket trial design and analysis includes methods that borrow information across tumor types to increase the quality of statistical inference within each tumor type. These methods can account for heterogeneity of response across tumor types and allow for enrollment of fewer participants per tumor type than traditional designs, an aspect that is particularly relevant for settings for rare tumor types with unmet medical needs. Recent reviews have discussed the general landscape of basket trials in oncology by focusing on the uptake of basket trials, the location where they are conducted, molecular targets, tumor types, observed response rates, and the risks and benefits of these trials when testing immunotherapy drugs. These reviews show that sophisticated information borrowing methodology, while advocated for in the statistical literature, has not been used often in practice. In this paper, we build on the existing systematic reviews of basket trials in oncology to discuss the current practices and landscape.We conceptually illustrate recent innovative methods for basket trials, with application to actual data from recently completed basket trials. We explore and discuss the extent to which innovative basket trials can be used to de-risk future trials through their ability to aid prioritization of promising tumor types for subsequent clinical development. We show that most basket trial designs in oncology were used in phase II trials and rarely used innovative methods. Most of the existing basket trial methods were developed for objective response rate or another binary endpoint. Basket trial design may increase the likelihood of success in the later confirmatory trials.